Activation of the IL-4/STAT6 Signaling Pathway Promotes Lung Cancer Progression by Increasing M2 Myeloid Cells - Fu, Cuiping; Jiang, Liyan; Hao, Shengyu; Liu, Zilong; Ding, Suling; Zhang, Weiwei; Yang, Xiangdong; Li, Shanqun (Frontiers in Immunology, 2019)
Emerging evidence shows that signal transducer and activator of transcription 6 (STAT6) plays critical roles in tumor development. We previously found high-level expression of STAT6 in human lung adenocarcinoma and squamous cell carcinoma, specifically in infiltrated immune cells located in the lung interstitium. Nevertheless, the role of STAT6 signaling in lung carcinogenesis and lung cancer proliferation, and its underlying mechanisms remain unclear. This study aimed to investigate the role of STAT6 as well as the interaction between STAT6 and the tumor microenvironment in pulmonary tumorigenesis. We established a murine model of primary lung carcinogenesis in STAT6-deficient (STAT6-/-) and STAT6 wild-type (WT) BALB/c mice using the carcinogen urethane. Two-month-old male mice were intraperitoneally injected with urethane (1 g/kg) dissolved in PBS (18). Primary tumors were monitored in vivo by positron emission tomography scanning. At 4, 6, and 9 months after urethane injection, lung tumors were harvested from the STAT6-/- and WT mice for analysis. Small interfering RNA was used to down-regulate the expression of STAT6 in tumor cells. Fluorescence activated cell sorting analysis was used to analyze fluorescence-conjugated cell markers. Transwell assays were used in co-culturing experiments. STAT6 protein expression was detected by western blotting, immunohistochemistry, and immunofluorescence. STAT6 mRNA expression was detected by quantitative real time-polymerase chain reaction. Cell Counting Kit-8 and colony formation assays were performed to evaluate cell proliferation. We detected high expression of STAT6 in CD11b+ cells of lung carcinoma. Our results indicate that STAT6 deficiency inhibits carcinogen-induced tumor growth and improves prognosis. STAT6 deficiency also decreased the mobilization and differentiation of CD11b+ cells. STAT6 deficiency in CD11b+ cells but not tumor cells decreased interleukin-4 (IL-4) secretion and the differentiation of CD11b+ cells into M2 macrophage cells. In conclusion, our findings indicate that IL-4/STAT6 signaling in CD11b+ cells promotes lung cancer progression by triggering an IL-4 positive feedback loop and increasing M2 myeloid cells. STAT6 may be a new therapeutic target for the prevention and treatment of lung cancer.